Parasite multiplication potential and the severity of Falciparum malaria. - Chotivanich, K; Udomsangpetch, R; Simpson, J; Newton, P; Pukrittayakamee, S; Looareesuwan, S; White, N (2000)
The multiplication rates and invasiveness of Plasmodium falciparum parasites isolated from adult Thai patients hospitalized with uncomplicated malaria (n=34) were compared with those from persons with severe malaria (n=42). To simulate severe malaria and control for host effects, the in vitro cultures were adjusted to 1% parasitemia and used the same red blood cell donor. P. falciparum isolates from persons with severe malaria had initial cycle multiplication rates in vitro that were 3-fold higher than those from uncomplicated malaria (median [95% confidence interval], 8.3 [7. 1-10.5] vs. 2.8 [1.7-3.9]; P=.001). Parasites causing severe malaria exhibited unrestricted red blood cell invasion, whereas those from uncomplicated malaria were restricted to a geometric mean of 40 (31%-53%) of red blood cells. P. falciparum parasites causing severe malaria were less selective and multiplied more at high parasitemias than those causing uncomplicated malaria.